Lipid Metabolism and its Relationship with Cardiovascular Diseases from a Biochemical and Genetic Approach - Myriam Lizeth Morales Pilataxi; Angélica Victoria Herrera Martínez; Diego Eduardo Guato Canchinia; Cristian Javier Calle Cárdenas (Revista Finlay, 2024)
Cardiovascular diseases are a global health concern, and are one of the main causes of morbidity and mortality worldwide. The background of cardiovascular diseases reveals the importance of understanding the underlying molecular mechanisms, given their high prevalence and repercussions on public health. It is necessary to understand the relationship between lipid metabolism and these diseases from a biochemical and genetic perspective; biochemical aspects are important for the development of more precise therapeutic approaches and prevention strategies. The objective of the research was to describe the relationship between lipid metabolism and cardiovascular diseases from a biochemical and genetic approach. The information search was carried out in the PubMed and ScienceDirect databases using the Boolean operators AND and OR, for English and Spanish. A total of 30 bibliographic references were obtained. The results revealed the influence of lipid metabolism in the control or development of cardiovascular diseases. Control of various key elements in both lipid metabolism and transport has proven effective in reducing these diseases.